Isolation and characterization bacteriophage for vibriosis therapy in fish - Mohammad Tamrin Mohamad Lal (2016)
"Bacterial infections in aquaculture are commonly treated using antibiotics. However, due to health concern and environmental issues, new control strategies for bacterial diseases are needed. Therefore, this study was conducted to isolate and characterize bacteriophage that are potentially be used as therapy for fish bacterial diseases. Four species of bacterial pathogens ( Vibrio alginolyticus, V. halVeyi, V. parahaemo/yticus and Photobacterium damselae) were targeted for bacteriophage isolation. Each bacteriophage isolate was spotted onto different bacterial pathogens (V. alginolyticus, V. halVeyi, V. parahaemolyticus and Ph. damselae) lawns. The bacteriophage morphology was determined using TEM and the whole genome sequence of bacteriophage was achieved using IIIumina sequencing and de novo assembly. The stability of the bacteriophage was evaluated on different levels of pH, temperatures and bile concentrations. The bactericidal effect of the bacteriophage was evaluated using the in vitro co-culture method. In addition, the toxicity of the bacteriophage was evaluated against brine shrimp (Artemia sp.) and Asian seabass (lates calcarifet} juveniles. This study has successfully isolated bacteriophage which were effective against V. alginolyticus, V. halVeyi and V. parahaemolyticus. The bacteriophage isolates exhibited high specificity to its host with exception to V. halVeyi phage that was also capable of infecting V. parahaemolyticus ATCC 17802. All phage isolates were classified under the double stranded DNA phage. The TEM analysis revealed that the v. alginolyticus phage, V. halVeyi phage and V. parahaemolyticus phage were belong to the Family of Myoviridae, Myoviridae and Siphoviridae, respectively. The complete genome of V. a/ginolyticus phage was estimated at 248,088 bp and has high homology to Vibrio phage VH7D. Meanwhile, V. parahaemolyticus phage genome was 56,637 bp and hypothetically novel. Interestingly, all the phages possess methylated genome. The bioinformatics analyses revealed that the phage genomes have low significant homologies to vibrio virulent genes and toxin related proteins. All phage isolates were stable at 50°C but completely deactivated at temperatures higher than 60 0c. The phage also stable at wide range of pH (4-9?) and high bile concentrations. Further analysis showed that the V. parahaemolyticus phage required high level of multiplicity of infection (MOl 100) to suppress the growth of its host but V. halVeyi and V. alginolyticus phages required low MOl (0.01) to achieve similar effect. The findings of this study showed that the characteristics of the bacteriophage complied with the phage therapy . requirement whereby all phages exhibited bactericidal effect and highly specific. The methylated genome allows the bacteriophage to survive from the defence mechanisms of the host bacteria. Lack of virulence genes prohibits the phage from contributing virulence to host bacteria through horizontal gene transfer. Furthermore, the phages were stable in both acidic and alkaline conditions which make them withstand the extreme condition of the gastrointestinal environment during therapy through oral administration. Most importantly, the bacteriophage were not toxic to the target animals. With these characteristics, the isolated phages seem beneficial for therapeutic use against vibriosis in aquaculture.